2017
DOI: 10.1097/phm.0000000000000751
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill Walking Combined With Anodal Transcranial Direct Current Stimulation in Parkinson Disease

Abstract: A single session combining treadmill walking and anodal tDCS delivered over the motor cortex resulted in a specific modulation of the reciprocal Ia inhibition from the tibialis anterior to the soleus muscle. However, this acute effect did not result in improvements of gait parameters associated with treadmill walking in Parkinson disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 26 publications
2
28
0
4
Order By: Relevance
“…Overall, these data show that TMS can identify even subtle changes in the pathophysiology of the motor cortex and, as such, it may be more useful in the detection of very early stages of neurodegeneration than clinical observation alone. Indeed, the TMS profile we observed is similar to that reported by most of the studies in patients with early PD, [45][46][47][48][49][50][51] especially in the off-state, 87 thus suggesting that an early impairment of both glutamate and GABA might be detectable in RBD even in the absence of an overt extrapyramidal syndrome. 54 In agreement with this hypothesis, the occurrence of RBD in PD patients has been found to be associated more with neocortical, limbic, and thalamic denervation rather than nigro-striatal dopaminergic denervation, thus reasonably indicating a different etiology and pathophysiology compared to the typical PD manifestations.…”
Section: Main Findingssupporting
confidence: 86%
See 1 more Smart Citation
“…Overall, these data show that TMS can identify even subtle changes in the pathophysiology of the motor cortex and, as such, it may be more useful in the detection of very early stages of neurodegeneration than clinical observation alone. Indeed, the TMS profile we observed is similar to that reported by most of the studies in patients with early PD, [45][46][47][48][49][50][51] especially in the off-state, 87 thus suggesting that an early impairment of both glutamate and GABA might be detectable in RBD even in the absence of an overt extrapyramidal syndrome. 54 In agreement with this hypothesis, the occurrence of RBD in PD patients has been found to be associated more with neocortical, limbic, and thalamic denervation rather than nigro-striatal dopaminergic denervation, thus reasonably indicating a different etiology and pathophysiology compared to the typical PD manifestations.…”
Section: Main Findingssupporting
confidence: 86%
“…Most of previous studies found changes of both SICI and ICF in patients with PD, including those in the early stage, in terms of decreased SICI and reduced ICF, suggesting a disinhibition and hypofacilitation of the motor cortex. [45][46][47][48][49][50][51] To date, conversely, only one TMS study has been carried out in idiopathic RBD patients, 52 reporting an impairment of the short-latency afferent inhibition (SAI) and supporting the hypothesis of cholinergic dysfunction in those who develop cognitive impairment. This finding was also found in a second study by the same research group on patients with RBD associated to PD, again interpreted as the result of a cholinergic involvement correlated with their cognitive decline.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Anodal tDCS may also induce dopamine release in the basal ganglia by the activation of glutamatergic corticostriatal fibers (Siebner et al, 1999;Fregni et al, 2006;Valentino et al, 2014). Studies have been done by targeting either the motor cortex (M1, 1-2 mA, 13-30 min) (Verheyden et al, 2013;Kaski et al, 2014b;Mak and Yu, 2014;Valentino et al, 2014;Costa-Ribeiro et al, 2016Schabrun et al, 2016;Fernandez-Lago et al, 2017;da Silva et al, 2018;Yotnuengnit et al, 2018) or the dorsolateral prefrontal cortex (DLPFC, 2 mA, 7-20 min) (Manenti et al, 2014;Lattari et al, 2017). At post-stimulation, a short-term benefit in gait was noted in most of these studies.…”
Section: Transcranial Direct Current Stimulation Idiopathic Parkinsonmentioning
confidence: 99%
“…• Gait and balance (Benninger et al, 2010;Verheyden et al, 2013;Capecci et al, 2014;Kaski et al, 2014a;Mak and Yu, 2014;Manenti et al, 2014;Valentino et al, 2014;Costa-Ribeiro et al, 2016Schabrun et al, 2016;Swank et al, 2016;Fernandez-Lago et al, 2017;Lattari et al, 2017;Criminger et al, 2018;da Silva et al, 2018;Dagan et al, 2018;Harris et al, 2018;Yotnuengnit et al, 2018;Alizad et al, 2019;Putzolu et al, 2019) • Upper limb function (Fregni et al, 2006;Benninger et al, 2010;Doruk et al, 2014;Salimpour et al, 2015;Costa-Ribeiro et al, 2016;Ferrucci et al, 2016;Schabrun et al, 2016;Cosentino et al, 2017;Ishikuro et al, 2018;Broeder et al, 2019) • Cognition (Nitsche et al, 2005;Boggio et al, 2006;Biundo et al, 2015;Manenti et al, 2016;Elder et al, 2017;Lawrence et al, 2018;Adenzato et al, 2019) • Impulsive pathological gambling behavior (Benussi et al, 2017a) • Speech (Pereira et al, 2013) • Sleep (Hadoush et al, 2018) • Fatigue …”
Section: Mode Of Tesmentioning
confidence: 99%
“…Emerging research suggests the potential for a-tDCS over the primary motor cortex (M1) to improve gait difficulties in PD due to the dense connectivity of the cortex and the basal ganglia, and the possibility of targeting the basal ganglia-thalamocortical motor circuits [ 22 27 ]. However, results from previous studies have indicated that the effects of tDCS on gait speed [ 24 , 26 34 ] and stride length [ 24 , 27 , 32 ] have been variable and appear to be dependent on stimulation site and electrode size. In one study, bilateral a-tDCS (3.5 × 5 cm 2 ) of either premotor and motor or prefrontal cortices with the cathode (5 × 5 cm 2 ) over the mastoid demonstrated significant improvement in gait speed [ 28 ].…”
Section: Introductionmentioning
confidence: 99%